2017
DOI: 10.1093/ckj/sfx109
|View full text |Cite
|
Sign up to set email alerts
|

First UK case report of kidney transplantation from an HIV-infected deceased donor to two HIV-infected recipients

Abstract: Kidney transplantation is now considered the treatment of choice for many human immunodeficiency virus (HIV)-infected patients with end-stage renal disease (ESRD). Graft survival rates using HIV-negative donors and carefully selected HIV-positive ESRD patients are similar to those observed in HIV-uninfected kidney transplant recipients. To address the relative shortfall in donated organs it has been proposed that organs from HIV-infected deceased donors might be allocated to HIV-infected patients on the transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 5 publications
3
6
0
Order By: Relevance
“…The finding of excellent patient and graft survival is consistent with reports from the South Africa cohort 17,18 and international case reports of HIV D+/R+ KT. 13,31,32 In South Africa, 1-year patient and graft survival were good (87% and 96%), 17,18 and although there was no HIV D−/R+ group for comparison, their outcomes were generally similar to that has been reported in other studies. 21,33 In the South Africa cohort, there were 6 deaths in the first year whereas there were no deaths in our study with a median of 1.7 years of follow-up.…”
Section: Discussionsupporting
confidence: 76%
“…The finding of excellent patient and graft survival is consistent with reports from the South Africa cohort 17,18 and international case reports of HIV D+/R+ KT. 13,31,32 In South Africa, 1-year patient and graft survival were good (87% and 96%), 17,18 and although there was no HIV D−/R+ group for comparison, their outcomes were generally similar to that has been reported in other studies. 21,33 In the South Africa cohort, there were 6 deaths in the first year whereas there were no deaths in our study with a median of 1.7 years of follow-up.…”
Section: Discussionsupporting
confidence: 76%
“…Another similar case was recently published by UK authors that showed a good outcome after two years of follow‐up in two HIV‐infected recipients who received a kidney from an HIV‐infected deceased donor …”
Section: Discussionsupporting
confidence: 61%
“…These positive results, together with the chronic scarcity of available organs, have encouraged the idea of using organs from HIV‐positive donors for select HIV‐positive recipients, and the initial experiences seem to suggest promising short‐term outcomes …”
Section: Introductionmentioning
confidence: 99%
“…stable infection of recipient cells) versus transient donor viremia is unclear. Additional cases reports of HIV D+/R+ liver and kidney transplant in Europe and North America have been published without major complications or breakthrough viremia (63,(116)(117)(118).…”
Section: Hiv Superinfection and Resistant Virusmentioning
confidence: 99%